INDOOR HI-INTENSIVE REARING OF FRY OF CIRRHINUS MRIGALA VERSUS TRADITIONAL REARING - Jain, A K (Indian Journal of Fisheries, 2011)
Through use of formulated feed and artificial aeration, it was possible to rear fry of Cirrhinus mrigala ata two times higher stocking density as compared to the traditional practice in nursery ponds. The useof aquarium, provided congenial indoor environment for the rearing of fry by avoiding the use of rawcattle dung and facilitated monitoring and control over physico-chemical qualities of water. The formulatedfeed contained cobalt chloride, vitamin B complex, vitamin C and oxytetracycline hydrochloride.The feeding of semi boiled microfined chicken egg yolk to fry provided all the essential amino acids.The average growth and survival rates in aquarium with the feeding of formulated feed and egg yolkwere 1.378 mm/day and > 99% respectively. The growth and survival rates in nursery pond with thefeeding of formulated feed alone were 0.979 mm/day and 83.3% respectively, while in control nurseryponds with traditional supplementary feed, these were 0.745 mm/ day and 73.37% respectively. Thusaquarium rearing has resulted in the saving of 25% time and approximately 30% fodder per lot of fryreared.